2016
DOI: 10.1084/jem.20160530
|View full text |Cite
|
Sign up to set email alerts
|

Peptidylarginine deiminase 4 promotes age-related organ fibrosis

Abstract: Peptidylarginine deiminase 4 (PAD4) citrullinates proteins. In neutrophils, it causes chromatin decondensation and release of NETs, which are injurious. Martinod et al. show in this study that NETs promote fibrosis in a cardiac model and that PAD4-deficient mice have reduced age-related organ fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
160
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(173 citation statements)
references
References 85 publications
12
160
1
Order By: Relevance
“…3 Elegant studies recently demonstrated that mice unable to form NETs are indeed protected from the development of fibrosis in the heart and lungs. 44 We found that the predominant protease within NETs, neutrophil elastase, is key to the induction of EndMT by NETs. Its mode of action involved the proteolysis of endothelial VE-cadherin, a known substrate of elastase, 23 and the subsequent activation of β-catenin signaling.…”
Section: Discussionmentioning
confidence: 74%
“…3 Elegant studies recently demonstrated that mice unable to form NETs are indeed protected from the development of fibrosis in the heart and lungs. 44 We found that the predominant protease within NETs, neutrophil elastase, is key to the induction of EndMT by NETs. Its mode of action involved the proteolysis of endothelial VE-cadherin, a known substrate of elastase, 23 and the subsequent activation of β-catenin signaling.…”
Section: Discussionmentioning
confidence: 74%
“…A brief collection of recent studies investigating potential impact of different leukocyte subsets in RILF is provided in supplemental Table S1, Supporting Information. Segregated‐nucleus‐containing atypical monocytes (SatM) with granulocyte characteristics regulated by CCAAT/enhancer binding protein β (C/EBPβ) as well as release of neutrophil extracellular traps (NETosis) consisting of extracellular chromatin orchestrated by peptidylarginine deiminase 4 (PAD4) in age related organ fibrosis . However, we found no dose dependent regulation of surrogates for SatM and NETosis on transcriptional and proteome level in our RILF model (data not shown).…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, PAD4 −/− , a murine model incapable of NETosis, displays smaller infarct size and has significantly better heart function, demonstrated by an elevated ejection fraction subsequent to an ischemic event (14). In aged or diabetic mice, neutrophils are primed for NETosis, producing excessive thrombosis and inflammation (15). Myocardial NET deposition delays wound healing, leading to fibrosis in the cardiac pressure-overload model.…”
Section: Immunology Of Inflammation As It Pertains To the Vessel Wallmentioning
confidence: 99%
“…Intriguingly, spontaneous fibrosis of organs produced by aging is greatly reduced in PAD4 −/− mice. Functionally, PAD4 −/− hearts are comparable to young murine hearts, and their systolic and diastolic function does not decline with age (15). Thus, there is recent interest in further study of the specific roles of neutrophils, NETosis, and the PAD4 pathway in atherosclerosis.…”
Section: Immunology Of Inflammation As It Pertains To the Vessel Wallmentioning
confidence: 99%